Navajo Multi-Household Social Units Archaeology on Black Mesa, Arizona - Rocek, Thomas R. (University of Arizona Press, 2022)
In a rigorous and innovative study, Thomas R. Rocek examines the 150-year-old ethnohistorical and archaeological record of Navajo settlement on Black Mesa in northern Arizona. Rocek's study, the first of its kind, not only reveals a rich array of interacting factors that have helped to shape Navajo life during this period but also constructs a valuable case study in archaeological method and theory, certain to be useful to other researchers of nonurban societies. Rocek explores a neglected but major source of social flexibility in these societies. While many studies have focused on household and community-level organization, few have examined the flexible, intermediate-sized, "middle-level" cooperative units that bind small groups of households together. Middle-level units, says the author, must be recognized as important sources of social flexibility in many such cultural contexts. Futhermore, attention to middle-level units is critical for understanding household or community-level organization, because the flexibility they offer can fundamentally alter the behavior of social units of a larger or smaller scale. In examining the archaeological record of Navajo settlement, Rocek develops archaeological methods for examing multiple-household social units (variously called "outfits or "cooperating groups") through spatial analysis, investigates evidence of change in middle-level units over time, relates these changes to economic and demographic flux, and compares the Navajo case study to the broader ethnographic literature of middle-level units. Rocek finds similarities with social organization in non-unilineally organized societies, in groups that have been traditionally described as characterized by network organization, and particularly in pastoral societies. The results of Rocek's study offer a new perspective on variability in Navajo social organization while suggesting general patterns of the response of social groups to change. Rocek's work will be of significant interest not only to those with a professional interest in Navajo history and culture, but also, for its methodological insights, to a far broader range of archaeologists, social anthropologists, ethnohistorians, ethnoarchaeologists, historians, cultural geographers, and political scientists.